Using the Behaviour Change Wheel and modified Delphi method to identify behavioural change techniques for improving adherence to smoking cessation medications - Amanual Getnet Mersha; Michelle Kennedy; Parivash Eftekhari; KS Kylie Lee; Penney Upton; Catherine Segan; Melissa A. Jackson; Kirsty Jennings; Gillian Sandra Gould (BMC, 2023)
Abstract Background Medication adherence is a crucial component of the pharmacological treatment of smoking. Previous interventions targeted to improve adherence to smoking cessation medications (SCMs) were designed using pragmatic approaches. This study aims to develop a comprehensive intervention strategy to improve adherence to SCMs using the Behaviour Change Wheel (BCW) and a modified Delphi method. Methods Recommendations for the design of intervention strategies were based on the BCW guide and six studies conducted by the research team. Factors related to healthcare providers and consumers (person making a quit attempt) that showed associations with adherence were mapped into the Capability, Opportunity, Motivation, Behaviour (COM-B) model, and corresponding intervention functions and policy categories. Interventions were then represented using the Behaviour Change Technique Taxonomy. Finally, a modified Delphi study using 17 experts was conducted to evaluate the nominated strategies using the Acceptability, Practicability, Effectiveness, Affordability, Side-effects, and Equity (APEASE) criteria. Results Following a stepped approach, an adherence support wheel was designed to guide implementation strategies and programmes. Thirteen intervention strategies were selected. The selected interventions include providing detailed instructions on how to use SCMs; establishing realistic expectations from SCMs; and providing training for healthcare providers regarding comprehensive smoking cessation care with specifics on the provision of adherence support. Conclusion The BCW guide and a modified Delphi were applied successfully to design interventions tailored to improve adherence to SCMs. Improving adherence to SCMs requires a comprehensive intervention approach involving various stakeholders. Future research is needed to assess the effectiveness of the nominated intervention strategies.